Ultrastructural changes of Henle's loop epithelial cells in the kidney of mice treated with low doses of Ochratoxin A - Aguirre, José Ignacio (1994)
Renal changes in mice daily treated with low doses of ochratoxin A (OA; 50-400μg/kg) for up to 4 weeks were investigated by electron microscope. Except the mice treated with 50μg/kg of OA for 4 weeks, all treated mice showed the following changes in the epithelial cells of Henle's loop: (1) degeneration of mitochondria, (2) increment of endoplasmic reticula, and (3) increase in the number and size of lysosomes and myelin figures.